Islamic Education Management at SD Islam Terpadu Muhammadiyah Kota Sungai Penuh - Yuserizal Bustomi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Abstract: Islamic Education Management at SD Islam Terpadu Muhammadiyah Kota Sungai PenuhThe main objective of the study was to determine the methods used by Islamic schools to teach Islamic principles to primary school students. This study uses a qualitative approach, describing the data more deeply, by collecting information through in-depth interviews and observations. SD Islam Terpadu Muhammadiayah Kota Sungai Penuh is the subject of this study. Data were collected using interviews and observations. The study mainly focuses on three important components of Islamic education management: financial management, asset and supply management, and curriculum management. The results showed that Islamic education management at Muhammadiayah Integrated Islamic Primary School in Sungai Penuh is categorized and follows the characteristics and principles of Islamic education management and the school promotes democratic and cooperative ideals in frequent debates over curriculum creation and evaluation. The research conclusion reveals that the curriculum management used is by the characteristics and principles of Islamic education management, the school applies the principle of efficient and successful production by cooperating with the Ummi institution to equip students with comprehensive Quranic studies.Abstrak: Manajemen Pendidikan Islam di SD Islam Terpadu Muhammadiyah Kota Sungai PenuhTujuan utama penelitian adalah untuk menentukan metode yang digunakan oleh sekolah Islam untuk mengajarkan prinsip-prinsip Islam kepada siswa sekolah dasar. Studi ini menggunakan pendekatan kualitatif, menggambarkan data lebih dalam, dengan mengumpulkan informasi melalui wawancara dan pengamatan mendalam. SD Islam Terpadu Muhammadiayah Kota Sungai Penuh adalah subjek penelitian ini. Pengumpulan data menggunakan wawancara dan observasi. Studi ini terutama berfokus pada tiga komponen penting dari manajemen pendidikan Islam: manajemen keuangan, manajemen aset dan pasokan, dan manajemen kurikulum. Hasil penelitian menunjukkan bahwa Manajemen Pendidikan Islam di SD Islam Terpadu Muhammadiayah Kota Sungai Penuh dikategorikan dan mengikuti karakteristik dan prinsip manajemen pendidikan Islam dan sekolah mempromosikan cita-cita demokratis dan kooperatif dalam perdebatan yang sering terjadi mengenai pembuatan dan evaluasi kurikulum. Kesimpulan penelitian mengungkap bahwa pengelolaan kurikulum yang digunakan telah sesuai dengan ciri dan prinsip manajemen pendidikan Islam, Sekolah menerapkan prinsip produksi yang efisien dan sukses dengan bekerja sama dengan lembaga Ummi untuk membekali siswa dengan kajian Al-Quran yang komprehensif.